Historical assembly of seasonally dry tropical forest diversity in the tropical Andes - Sarkinen, T (2010)
The relative contributions of biome history and geological setting to historical assembly of species richness in biodiversity hotspots remain poorly understood. The tropical Andes is one of the world’s top biodiversity hotspots, and with its diverse biomes and the relatively recent but dramatic uplift, the Andes provides an ideal study system to address these questions. To gain insights into the historical species assembly of the tropical Andes, this study focuses on investigating patterns of plant species diversification in the Andean seasonally dry tropical forest (SDTF) biome. Three plant genera are used as study groups: Amicia (Leguminosae, Papilionoideae), Tecoma (Bignoniaceae), and Mimosa (Leguminosae, Mimosoideae). Species limits are re-evaluated to enable dense sampling of species and intraspecific diversity for phylogeny reconstruction for each group. Time-calibrated phylogenies for Amicia and Mimosa are presented and used to determine patterns of species diversification in time and space. For Tecoma, incongruence between nuclear and chloroplast gene trees precludes straightforward estimation of a species tree and this incongruence is attributed to possible reticulation caused by hybridization. Divergence time estimates and patterns of diversification for Amicia and Mimosa are compared with other Andean SDTF groups (Cyathostegia, Coursetia, Poissonia; Leguminosae) using isolation by distance and phylogenetic geographic structure analyses. Consistently deep divergences between sister species and high geographic structure across all five groups suggest that Andean SDTF lineages have persisted over the past 10 million years (My) with high endemism driven by dispersal limitation, caused by geographic isolation, following the most recent episode of rapid mountain uplift 5-10 My ago. This prolonged stasis of the Andean SDTF biome is in line with Miocene fossil and paleoclimate evidence. Finally, wider analyses of the contrasting evolutionary timescales of older SDTF and more recent high-altitude grassland diversity suggest that the exceptional plant species diversity in the Andes is the outcome of highly heterogeneous evolutionary histories reflecting the physiographical heterogeneity of the Andean biodiversity hotspot.